Getting started in financial information - Moreau, Daniel 1949- (Getting started in, 2000)
Finding information on investing is easy. Making sense of it all is not. This straightforward guide clears up any confusion readers may have. Covering all the basics of investing, it will help readers make smarter decisions by showing them what to look for in stock tables, how to read between the lines of a fund prospectus, and distinguishing between fact and opinion when it comes to the so-called financial "experts." Making this text an invaluable introduction to investing facts, figures, and fundamentals.